Effect of adding rosemary powder (Ros marinus oficinalis) on some blood chemistries and liver function in the serum of ROSS breed meat chickens. (Sebha University Conference Proceedings, 2024)
This  study was conducted in one of the farms located south of the city of Sirte in May 2023, and 45 14-day-old Ross breed meat chicks were used in the study, which were randomly distributed in three groups and each group was divided into three replicates and each replicate had 5 birds, and the treatments were as follows: The control treatment (witness 0%) is a standard leech, the second treatment is a standard leech supplemented with rosemary powder (0.3 g/kg feed), the third treatment is a standard leech supplemented with rosemary powder (0.6 g/kg feed), the experiment continued until the birds reached the age of 45 days and blood samples were taken, and the experiment included the evaluation of the following characteristics: The results of the study indicated that there was a significant difference (P˂0.05) in the level of blood glucose in the first treatment added (0.3 rosemary powder), compared to the control treatment (witness 0%) and the second treatment (0.6 rosemary powder), and a significant difference (P>0.05) in GOT for the treatment (witness 0%) compared to the rest of the treatments. There was also a significant  difference (P>0.05) in ALK in the second treatment (0.6 rosemary powder) compared with the treatment (0% witness) and the first treatment added (0.3 rosemary powder), while there were no changes in mean blood lipids, total cholesterol, and triglycerides and there was no significant effect (P>0.05) on the level of liver function of the subjects. 05) For the level of liver function for the averages of enzymes, GPT, total protein, and albumin globulin, there was a clear and significant improvement in liver enzymes by lowering liver enzymes, which confirms the role of the plant in protecting the liver due to the presence of flavonoids.